The pharmacodynamics-based prophylactic benefits of GLP-1 receptor agonists and SGLT2 inhibitors on neurodegenerative diseases: evidence from a network meta-analysis - Tseng, Ping-Tao; Zeng, Bing-Yan; Hsu, Chih-Wei; Hung, Chao-Ming; Carvalho, Andre F.; Stubbs, Brendon; Chen, Yen-Wen; Chen, Tien-Yu; Lei, Wei-Te; Chen, Jiann-Jy; Su, Kuan-Pin; Shiue, Yow-Ling; et al. (BMC medicine, 2025)
Glucagon-like peptide-1 (GLP-1) receptor agonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors represent a new generation of antihyperglycemic agents that operate through mechanisms distinct from conventional diabetes treatments. Beyond their metabolic effects, these medications have demonstrated neuroprotective properties in preclinical studies. While clinical trials have explored their therapeutic potential in established neurodegenerative conditions, their role in disease prevention remains unclear. We conducted a network meta-analysis (NMA) to comprehensively evaluate the prophylactic benefits of these agents across multiple neurodegenerative diseases and identify the most promising preventive strategies. We systematically searched PubMed, Embase, ClinicalKey, Cochrane CENTRAL, ProQuest, ScienceDirect, Web of Science, and ClinicalTrials.gov through October 24th, 2024, for randomized controlled trials (RCTs) of GLP-1 receptor agonists or SGLT2 inhibitors. Our primary outcome was the incidence of seven major neurodegenerative diseases: Parkinson's disease, Alzheimer's disease, Lewy body dementia, multiple sclerosis, amyotrophic lateral sclerosis, frontotemporal dementia, and Huntington's disease. Secondary outcomes included safety profiles assessed through dropout rates. We performed a frequentist-based NMA and evaluated risk of bias with Risk of Bias tool. The main result of the primary outcome in the current study would be re-affirmed via sensitivity test with Bayesian-based NMA. Our analysis encompassed 22 RCTs involving 138,282 participants (mean age 64.8 years, 36.4% female). Among all investigated medications, only dapagliflozin demonstrated significant prophylactic benefits, specifically in preventing Parkinson's disease (odds ratio = 0.28, 95% confidence intervals = 0.09 to 0.93) compared to controls. Neither GLP-1 receptor agonists nor other SGLT2 inhibitors showed significant preventive effects for any of the investigated neurodegenerative conditions. Drop-out rates were comparable across all treatments. This comprehensive NMA reveals a novel and specific prophylactic effect of dapagliflozin against Parkinson's disease, representing a potential breakthrough in preventive neurology. The specificity of dapagliflozin's protective effect to Parkinson's disease might rely on its highly selective inhibition to SGLT2. These findings provide important direction for future research and could inform preventive strategies for populations at risk of Parkinson's disease. PROSPERO CRD42021252381.